Prevalence of social frailty and its associated factors in the older Chinese population: a national cross-sectional study - Xin Qi; Yingying Li; Jiabin Hu; Lingbing Meng; Ping Zeng; Jing Shi; Na Jia; Xuezhai Zeng; Hui Li; Qiuxia Zhang; Juan Li; Deping Liu (BMC Geriatrics, 2023)
Abstract Background Social frailty has not been comprehensively studied in China. Our objective is to investigate the prevalence of social frailty among the older population in China, as well as identify relevant factors and urban-rural differences. Methods We obtained data from the Fourth Sample Survey of the Aged Population in Urban and Rural China (SSAPUR) database. The study employed a multistage, stratified, cluster-sampling method, recruiting a total of 224,142 adults aged 60 years or older. Participants were interviewed to gather demographic data and information on family, health and medical conditions, health care service status, living environment conditions, social participation, protected rights status, spiritual and cultural life, and health. Social frailty was assessed using the HALFE Social Frailty Index. A score of three or above indicated social frailty. Results We analyzed a total of 222,179 cases, and the overall prevalence of social frailty was found to be 15.2%. The highest prevalence was observed among participants aged 75–79 years (18.0%). The prevalence of social frailty was higher in rural older populations compared to urban older populations (19.9% in rural vs. 10.9% in urban, P < 0.0001). In urban areas, women had a higher prevalence than men (11.7% in women vs. 9.9% in men, P < 0.0001), while in rural areas, men had a higher prevalence than women (20.6% in men vs. 19.2% in women, P < 0.0001). Multivariate regression analysis revealed that living in a rural/urban environment (OR 1.789, 95% CI 1.742–1.837), absence of a spouse/spousal presence (OR 4.874, 95% CI 4.743–5.009), self-assessed unhealthy/health status (OR 1.696, 95% CI 1.633–1.761), and housing dissatisfaction/satisfaction (OR 2.303, 95% CI 2.233–2.376) were all significantly associated with social frailty. Conclusions Using the HALFE social frailty index, we found a prevalence of 15.2% among older people in China, with the highest prevalence observed in the 75–79 age group. Social frailty was more prevalent in rural areas than in urban areas. Various factors, including spousal presence, housing satisfaction, health status, and urban-rural residential differences, were significantly associated with social frailty. These findings highlight the modifiable and non-modifiable factors that contribute to social frailty among older individuals in China.